Adaptive wind energy harvester with transformable bluff body. (15th June 2021) - Jeon, Sehun; Sun, Wan; Jang, Hyeonho; Seok, Jongwon
Highlights: An adaptive energy harvester with a transformable bluff body was developed. A nonlinear coupled aero-electro-mechanical model was constructed. The transformation mechanism on the bluff body was thoroughly identified. A maximum of 39% increase ratio in the output power was obtained. Abstract: A novel adaptive wind energy harvester with a transformable bluff body responsive to external wind velocity is proposed in this study. This study is inspired by our finding that when an external wind velocity is lower than a specific (threshold) wind velocity, the energetic performance of an energy harvester with a certain cross-sectional shape of the bluff body is better than that with another shape and the reverse is true when the external wind speed is greater than the threshold. More specifically, the bluff body considered in the present study is composed of a prismatic cylinder and its cross-sectional shape is a triangle when the external wind velocity is below a certain threshold value. However, when the wind velocity exceeds the threshold value, the cross-sectional shape of the bluff body transforms into a W-shape in response to the wind velocity. In this study, an appropriate design process to develop the proposed system is established, and a physical prototype is fabricated. Thereafter, an associated mathematical model is developed and experimentally validated. The energetic and dynamic performances of the proposed system are thoroughly investigated and compared to systems with bluff bodies in three fixed cross-sectional shapes (square, triangle, and W-shape). As a result, the percentage increase ratio in the output power of the proposed energy harvester is found to be 23% higher than that of the system with a triangular bluff body, which is known to provide the best performance. This result indicates that the proposed system remarkably improves the energetic performance in comparison to the conventional system.